A retrospective comparative study of laparoscopic appendectomy and open appendectomy - Bhosle, R. V.; Degloorker, Ganesh Ganpatrao (International Surgery Journal, 2018)
Background: Appendectomy is the most common surgical procedure performed in emergency surgery. Appendectomy is the treatment of choice, which can be done either by open or laparoscopic approach. Controversies till exist as to which is the better choice among the two surgical procedures for treating appendicitis. In this retrospective analysis, we aimed to compare outcomes of laparoscopic appendectomy with open appendectomy. Methods: Total 120 appendectomy cases were analyzed retrospectively in a period of 2 years. The study was conducted in the department of surgery and Institutional ethical committee approval was obtained. Patient demographic data, intraoperative findings and postoperative clinical outcomes were collected standard data sheet. Biopsy specimens were sent to pathology department for histopathological evaluation to confirm the appendicitis. Results: There was no statistical difference found in demographic data of patient’s undergone appendectomy in both (OA and LA) procedures. The overall incidences of postoperative complications were significantly lower (P=.005) in laparoscopic appendectomy. The length of hospital stay was much shorter in laparoscopic appendectomy (3.5 days) when compared with open appendectomy (6.2 days). Conclusions: The laparoscopic appendectomy was better than open or conventional appendectomy with respect to less pain, shorter hospitalization period, minimal postoperative complications and early return to normal activity.